Brown Bowel Syndrome in a Middle-Aged Woman with Chronic Idiopathic Malabsorption. (4th April 2019) - Parente, Renato; Pinamonti, Maurizio; Martina, Stefania
Abstract : Brown bowel syndrome (BBS) is an extremely unusual condition characterized by an orange-brown discoloration of the bowel and intestinal motility disorders secondary to fat-soluble vitamin deficiency and malabsorption from many different causes. We present the case of a middle-aged woman suffering for years of chronic constipation with recurrent intestinal subocclusion, who was diagnosed BBS on surgical biopsy material. Nutritional supplementary treatment was tried, but her symptoms did not improve, and a decision was finally made in favor of a surgical approach. After subtotal colectomy and continual vitamin nutritional supplementation, she has now regular transit without the use of laxatives. BBS is a rare complication of long-term malabsorption manifesting as intestinal motility disorders, which can lead to severe complications. This condition is only partially responsive to vitamin supplementation, and most cases require surgery.